Identification of Attacks on Computer Networks Based on Neural Network Technologies in the MatLab / Simulink Modeling System - Мінаєв, Ю. М.; Лієс, Бенамур; Гузій, М. М.; Даниденко, В. В. (Proceedings of National Aviation University (archive), 2021)
The method of constructing a neural network for identifying attacks on computer networks with the help of means of the package of mathematical modeling MatLab / Nenrol Network / Simulink is given. An example illustrating the effectiveness of the peer-to-peer technology is given.